1987
DOI: 10.1002/mrc.1260251206
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 and phosphorus‐31 NMR spectroscopy of phenoxychlorocyclotriphosphazenes, N3P3Cl6‐n(OC6H5)n

Abstract: The "P and "C NMR spectra of all twelve phenoxychlorocyclotriphosphazenes of general formula N3P3Cb-,(OC6H5), (n = 1-6) were assigned in detail. With samples abundant in one homolog, but with a disparity between geometrical isomers, the signals due to the cis and trans isomers of N3P3C14(OC6H5)2 and N3P3Cl2(0C6H,), were also assigned. The "P chemical shifts and coupling constants correlate linearly with the level of substitution, n. The 13C NMR spectra exhibit complex multiplets for the ipso-and ortho-carbons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The eluent compositions used are listed in Table VI. The corresponding chemical shifts of the 31P NMR of each derivative obtained are listed in Table VII and compared with the reported data (Reuben, 1987). It was found that the condensation predominantly followed a nongeminal pathway (Allcock, 1972b).…”
Section: Resultsmentioning
confidence: 87%
“…The eluent compositions used are listed in Table VI. The corresponding chemical shifts of the 31P NMR of each derivative obtained are listed in Table VII and compared with the reported data (Reuben, 1987). It was found that the condensation predominantly followed a nongeminal pathway (Allcock, 1972b).…”
Section: Resultsmentioning
confidence: 87%
“…More recently, it has been used to synthesize a wide range of cyclotriphosphazene derivatives, such as cyclotriphosphazene hydrazides (Chandrasekhar et al, 2003), cyclotriphosphazene with N,N,N H ,N H -tetramethylguanidine groups (Bloy & Diefenbach, 2000), and cyclotriphosphazene with 2-, 3-and 4-pyridylmethoxy groups (Diefenbach et al, 1999). Its synthesis and NMR data have been described elsewhere (Reuben, 1987;Selvaraj et al, 1991). To date, however, structural data for (I) are not available in the Cambridge Structural Database (CSD, Version 5.24; Allen, 2002).…”
Section: Commentmentioning
confidence: 99%
“…We have shown that the enolate ion of acetaldehyde reacts with hexahalocyclotriphosphazenes N 3 P 3 X 6 [X = F, Cl( 1 )] and that these reactions are stereoselective showing a preference for the cis isomer in the reactions of 1 . The cis isomer is also preferred in the reactions hexahalocyclophosphazenes with aryloxides. , The (vinyloxy)pentachlorocyclotriphosphazene, N 3 P 3 X 5 (OCHCH 2 ) ( 2 ), has also been used as a monomer in free radical polymerization . Allcock and Schmutz have previously explored the reaction of the sodium salt of trifluoroethanol with 1 and have shown that there is a strong preference for formation of the non-geminal trans isomer .…”
Section: Introductionmentioning
confidence: 99%